Cultural factors in traditional Malay house - Abdul Rahim, Zaiton (IIUM Press, 2011)
The Malays and their culture are entwined in every aspect of their lives from birth till death. From the pre-Islamic days to gradual Islamic intervention through trading and missionary quests, the culture assimilated left marks in their built environment implicitly and explicitly. Through literature review and observations, this article thence described briefly the salient cultures ofthe Malays that affects the design ofthe traditional Malay houses we had inherited today. Perhaps through understanding of the features, younger generations may be able to reflect their roots and have pride in their rich and considerate cultural heritage.